Twentieth Century: The History of the World, 1901 to 2000 - Roberts, J. M. (Harmondsworth Viking, 1999)
One of our greatest contemporary historians greets the millennium with an authoritative and engrossing survey of the twentieth century. When it comes to narrative history, J. M. Roberts is an undisputed master of his craft. His classic History of the World (more than a quarter million copies sold worldwide) remains, in the words of eminent historian A. J. P. Taylor, "a stupendous achievement...the unrivaled World History of our day. . . unbelievably accurate... almost incontestable in its judgement." More remarkable, his History of Europe was acclaimed as "the best single volume history of Europe. . . combining authority and good sense with fluency and wit" (London Times Literary Supplement). In his latest sweeping and entertaining work, Roberts focuses on our own momentous century.Twentieth Century places a chronological narrative of events in the context of the long-term changes that colored them. Among these are worldwide increases in life expectancy; major strides in science and technology; the radical reconfiguration of the global economy; vanished empires, shrunken white hegemony, and reassessment of "western" civilization; and the ever-evolving role of women.
Keywords: 20th Century (1901-2000); History